Peran AI dalam Membangun Kesadaran Ekologis pada Peserta Didik Melalui Pendidikan Agama Islam - Sulaiman, Ahmad (Lembaga Peneltian Universitas Islam Internasional Darullughah Wadda'wah, 2024)
This article discusses the role of Artificial Intelligence (AI) in raising ecological awareness among students through Islamic religious education. By utilizing AI, education can become more interactive and adaptive, allowing the integration of ecological values that align with Islamic teachings. This study aims to identify the effectiveness of AI usage in Islamic religious education and its impact on students' ecological awareness. The results show that the integration of AI into the Islamic education curriculum can enhance students' understanding and concern for environmental issues.